The Efforts to Increase Teacher's Competence in Implementing A Scientific Learning Approach Through In House Training (IHT) - Aidawati Aidawati; Swasti Endriani (FKIP UNIVERSITAS PAKUAN, 2022)
This research aims to improve the competence of SMA Negeri 6 Bogor teachers in implementing a scientific learning approach through In House Training (IHT). The research was carried out for four months, from July to October 2019. Based on the results of the research, the results of the understanding of SMA Negeri 6 Bogor teachers on the scientific approach after the implementation of In House Training (IHT) increased. This could be seen from the results of the pre-test and post-test, namely the average results of 67.05 in the pre-test and 85.3 in the post-test. Good understanding in theory has correlation with practice. This could be seen from the results of peer teaching observations about the implementation of scientific learning approach with an average value of 80.85, the highest score of 85 obtained by 4 teachers, a score of 83 obtained by 2 people and there are still 50% of teachers who get a score between 70 -76.77. It could be concluded that the implementation of In House Training (IHT) is effective in increasing the competence of SMA Negeri 6 Bogor teachers in implementing the scientific learning approach.